THE IMPORTANCE OF ENGLISH LANGUAGE - Mamadiyorova, Feruza (Журнал иностранных языков и лингвистики, 2021)
Today , learning English is one of the most pressing issues . In this regards , this article discusses the study of English , its importance and benefits . The main factors of learning English are outlined.